Exploring ethyl pyruvate as an antifungal and antibacterial agent for food preservation: an in vitro and in silico study - Erarslan, Azime; Yuka, Selcen Ari (WILEY, 2024)
Food pathogens are one of the microbiological problems that have negative effects on both economic and human health by causing spoilage and decay of important foods such as fruits and vegetables. The adverse effects of chemical residues left by synthetic biocides on human health and the development of resistance mechanisms in microorganisms have directed research towards bio-fungicide. This study aimed to develop an effective bio-fungicide using varying concentrations of ethyl pyruvate (1-18 mu L disc(-1)). Additionally, the interaction of EP with several proteins in pathogenic bacteria and fungi was investigated through in silico molecular docking. According to the obtained results, an increase in EP concentration resulted in larger inhibition zone diameters. In this context, at an EP concentration of 18 mu L disc(-1), the inhibition zones formed against E. coli, S. aureus, L. monocytogenes and S. typhimurium bacteria were measured as 27.50 +/- 0.50 mm, 31.00 +/- 1.00 mm, 30.00 +/- 1.00 mm and 32.66 +/- 1.15 mm, respectively. EP at a concentration of 9 mu L disc(-1) showed a fungicidal effect against B. cinerea and P. expansum and a fungistatic effect against C. gloeosporioides. As a result of in silico tests, the molecular binding energies of EP with E. coli dihydrofolate reductase, S. aureus DNA Gyrase B and B. cinerea 14 alpha-demethylase were determined to be -4.62, -4.26 and -3.95 kcal mol(-1), respectively. Our results holistically revealed that EP has great potential for use in food preservation due to its antifungal and antibacterial properties.
Keywords: antibacterial activity; antifungal activity; DPPH radical scavenging capacity; ethyl pyruvate; foodborne pathogens; DECONTAMINATION; ENZYME; Food Science & Technology